Assessment of the CHA2DS2-VASc Score for the Prediction of Death in Elderly Patients With Coronary Artery Disease and Atrial Fibrillation - Wu, Yangxun; Wang, Guanyun; Dong, Lisha; Qin, Liu'an; Li, Jian; Yan, Hengming; Guo, Wenjie; Feng, Xiaodong; Zou, Yuting; Wang, Ziqian; Du, Rina; Zhang, Yuxiao; et al. (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Coronary artery disease (CAD) and atrial fibrillation (AF) often coexist and lead to a much higher risk of mortality in the elderly population. The aim of this study was to investigate whether the CHA2DS2-VASc score could predict the risk of death in elderly patients with CAD and AF. Methods: Hospitalized patients aged ≥ 65 years with a diagnosis of CAD and AF were recruited consecutively. Patients were divided into 5 groups according to the CHA2DS2-VASc score (≤ 2, =3, =4, =5 and ≥ 6). At least a 1-year follow-up was carried out for the assessment of all-cause death. Results: A total of 1579 eligible patients were recruited, with 582 all-cause deaths (6.86 per 100 patient-years) occurring during a follow-up of at least 1 year. With the increase in the CHA2DS2-VASc score, the 1-year and 5-year survival rate decreased (96.4% vs. 95.7% vs. 94.0% vs. 86.5% vs. 85.7%, respectively, P < 0.001; 78.4% vs. 68.9% vs. 64.6% vs. 55.5% vs. 50.0%, respectively, P < 0.001). Compared with the patients with CHA2DS2-VASc score < 5, for patients with CHA2DS2-VASc score ≥ 5, the adjusted hazard ratio for death was 1.78 (95% CI: 1.45-2.18, P < 0.001). The predictive values of the CHA2DS2-VASc score ≥ 5 for in-hospital (C-index = 0.66, 95% CI: 0.62-0.69, P < 0.001), 1-year (C-index = 0.65, 95% CI: 0.63-0.67, P < 0.001) and 5-year (C-index = 0.60, 95% CI: 0.59-0.61, P < 0.001) death were in comparable. Conclusion: In elderly patients with concomitant CAD and AF, the CHA2DS2-VASc score can be used to predict death with moderate accuracy.